Assessment of the aryl hydrocarbon receptor-mediated activities of polycyclic aromatic hydrocarbons in a human cell-based reporter gene assay - Vondráček, Jan; Pěnčíková, Kateřina; Neča, Jiří; Ciganek, Miroslav; Grycová, Aneta; Dvořák, Zdeněk; Machala, Miroslav (Environmental pollution (1987), 2017)
Activation of the aryl hydrocarbon receptor (AhR)-mediated activity is one of key events in toxicity of polycyclic aromatic hydrocarbons (PAHs). Although various classes of AhR ligands may differentially activate human and rodent AhR, there is presently a lack of data on the human AhR-inducing relative potencies (REPs) of PAHs. Here, we focused on estimation of the AhR-mediated activities of a large set of environmental PAHs in human gene reporter AZ-AhR cell line, with an aim to develop the human AhR-based REP values with potential implications for risk assessment of PAHs. The previously identified weakly active PAHs mostly failed to activate the AhR in human cells. The order for REPs of individual PAHs in human cells largely corresponded with the available data from rodent-based experimental systems; nevertheless, we identified differences up to one order of magnitude in REP values of PAHs between human and rodent cells. Higher REP values were found in human cells for some important environmental contaminants or suspected carcinogens, such as indeno[1,2,3-cd]pyrene, benz[a]anthracene or benzo[b]fluoranthene, while lower REP values were determined for methyl-substituted PAHs. Our results also indicate that a different rate of metabolism for individual PAHs in human vs. rodent cells may affect estimation of REP values in human cell-based assay, and potentially alter toxicity of some compounds, such as benzofluoranthenes, in humans. We applied the AZ-AhR assay to evaluation of the AhR-mediated activity of complex mixtures of organic compounds associated with diesel exhaust particles, and we identified the polar compounds present in these mixtures as being particularly highly active in human cells, as compared with rodent cells. The present data suggest that differences may exist between the AhR-mediated potencies of PAHs in human and rodent cells, and that the AhR-mediated effects of polar PAH derivatives and metabolites in human cell models deserve further attention.
Keywords: transkripční faktory bHLH; výfukové emise vozidel; buněčné linie; Genes, Reporter; Humans; Environmental Pollutants; polycyklické aromatické uhlovodíky; Cell Line; karcinogeny; Basic Helix-Loop-Helix Transcription Factors; biotest; lidé; reportérové geny; receptory aromatických uhlovodíků; Receptors, Aryl Hydrocarbon; Vehicle Emissions; Biological Assay; látky znečišťující životní prostředí; Polycyclic Aromatic Hydrocarbons; Carcinogens